Digital development of Slovenian wood industry Digitalni razvoj slovenske drvne industrije - Kropivšek, Jože; Grošelj, Petra (2020)
The research examined the digital development of the Slovenian wood industry, especially the implementation of the concept of Industry 4.0 into practice. Within this, the implementation of specific technological pillars was studied, with the emphasis on smart factories and smart, innovative products. In the empirical part of the research, we prepared a survey and interviewed selected managers and entrepreneurs. We compared answers regarding sub-sectors, the size of the companies and the level of digitalization. The general results show that around half of the surveyed companies are already implementing the Industry 4.0 concept into their businesses, while the rest are beginners when speaking about digitalization. The biggest obstacles to the implementation of the concept are the high investments in equipment and the lack of financial support from the state. The lack of digital competencies, which is especially prevalent among older workers, is another major barrier that businesses face. Only 30 % of the surveyed companies are engaged in the production of smart products. We can conclude that digitalization in the Slovenian wood industry is still at a relatively low level, but with the latest strategic orientations at both the state and business level, this situation will certainly improve in the near future.
U radu je predočeno istraživanje digitalnog razvoja slovenske drvne industrije, posebice istraživanje primjene koncepta Industrija 4.0 u praksi. Unutar toga proučavana je primjena specifičnih tehnoloških stupova s naglaskom na pametne tvornice i pametne, inovativne proizvode. U empirijskom dijelu istraživanja pripremili smo anketu i intervjuirali odabrane menadžere i poduzetnike. Usporedili smo odgovore koji se odnose na podsektore, veličinu poduzeća i razinu digitalizacije. Opći rezultati pokazuju da približno polovica anketiranih tvrtki u poslovanju već primjenjuje koncept Industrija 4.0, dok su ostale tvrtke početnici u digitalizaciji. Najveće su prepreke provedbi koncepta velika ulaganja u opremu i izostanak državne financijske potpore. Nedostatak digitalnih kompetencija, koji je osobito vidljiv među starijim radnicima, dodatna je velika prepreka s kojom se tvrtke suočavaju. Samo 30 % anketiranih tvrtki bavi se proizvodnjom pametnih proizvoda. Može se zaključiti da je digitalizacija u slovenskoj drvnoj industriji još uvijek na relativno niskoj razini, ali s najnovijim strateškim orijentacijama i na državnoj i na poslovnoj razini ta će se situacija u skoroj budućnosti sigurno poboljšati.
Bibliografija: 32 jed.
Abstract ; Sažetak.
Keywords: Drvna industrija -- Digitalizacija -- Industrija 4.0 -- Internet stvari; Slovenija